Effect of size, concentration, and nature of fillers on crystallinity, thermal, and mechanical properties of polyetheretherketone composites. Issue 5 (31st August 2021) - Doumeng, Marie; Berthet, Florentin; Delbé, Karl; Marsan, Olivier; Denape, Jean; Chabert, France
Abstract: Polyetheretherketone (PEEK) composites exhibit high stiffness, chemical stability, and heat resistance and they are therefore employed in applications under severe operating environments. This work aims to provide insight into the effect of the size, concentration, and type of fillers on the thermal and mechanical properties of PEEK. A total of 32 composites are used to highlight the influence of nature (lamellae, such as boron nitride and graphite and silicon carbide and alumina), size (nano and micrometric), and content (2.5, 5, 7.5, and 10 vol%) of fillers. The melting temperature and lamellar thickness did not change regardless of the nature of the filler. The thermomechanical analysis demonstrates that lamellar fillers form a percolating network and contribute significantly to the enhancement of the storage modulus. The increase in the storage modulus is proportional to the filler content, and it is more pronounced for micro composites. As expected, the percolating network is formed at lower concentrations for lamellar fillers than for spherical ones. The highest conductivity is achieved with graphite at 0.823 W m −1  K −1, which is twice that of PEEK for 10 vol%. Moreover, the use of micrometric fillers results in thermal conductivity enhancement attributed to the higher amount of efficient hot zones for heat transfer. Abstract : This work makes a step towards a better knowledge of the polyetheretherketone composites and the prediction of their properties. We assess the size, concentration and nature of fillers. The content of the filler seems to have a greater influence on thermal and mechanical properties. The fillers nature and size affect the crystalline structure.